Growing Plums in Florida - E. P. Miller; Peter C. Andersen; Jeffrey G. Williamson; James J. Ferguson; J. Bitter (EDIS)
Plum production has good potential for commercial growers and homeowners in Florida and other mild winter areas throughout the Gulf coast. However, most seasonal plums on the market are from California and will not perform well enough in Florida to produce fruit. From 1998 to 2001, plum cultivars have been released from the University of Florida's breeding program that adapt to our mild winters and high disease pressures. Because they have cropped reliably and produced high quality fruit, these cultivars are recommended for trial in Florida. The names of all University of Florida plum cultivars begin with the prefix 'Gulf.' These cultivars are Japanese type plums (Prunus salicina Lindl.) and have resistance to plum leaf scald (Xylella fastidiosa) and bacterial spot (Xanthomonas campestris). Fruit size is satisfactory (about 1 1/2 to 2 in. diameter) and fruit quality is good. They ripen in early to late May or about two weeks before California plums. This document is HS895, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2005.